Bioavailability of metalloporphyrin-based SOD mimics is greatly influenced by a single charge residing on a Mn site - Spasojevic, Ivan (2010)
In the cell Mn porphyrins (MnPs) likely couple with cellular reductants which results in a drop of total charge from 5+ to 4+ and dramatically increases their lipophilicity by up to three orders of magnitude depending upon the length of alkylpyridyl chains and type of isomer. The effects result from the interplay of solvation, lipophilicity and stericity. Impact of ascorbate on accumulation of MnPs was measured in E. coli and in Balb/C mouse tumours and muscle; for the latter measurements, the LC/ESI-MS/MS method was developed. Accumulation was significantly enhanced when MnPs were co-administered with ascorbate in both prokaryotic and eukaryotic systems. Further, MnTnHex-2-PyP(5+) accumulates 5-fold more in the tumour than in a muscle. Such data increase our understanding of MnPs cellular and sub-cellular accumulation and remarkable in vivo effects. The work is in progress to understand how coupling of MnPs with ascorbate affects their mechanism of action, in particular with respect to cancer therapy.